6(7x+1)=43x

Simple and best practice solution for 6(7x+1)=43x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(7x+1)=43x equation:


6(7x+1)=43x

We simplify the equation to the form, which is simple to understand
6(7x+1)=43x

Reorder the terms in parentheses
+(+42x+6)=43x

Remove unnecessary parentheses
+42x+6=+43x

We move all terms containing x to the left and all other terms to the right.
+42x-43x=-6

We simplify left and right side of the equation.
-1x=-6

We divide both sides of the equation by -1 to get x.
x=6

See similar equations:

| 7x-7=3x+10 | | x^2-((2/3)*x)-(27/16) | | x^2-(2/3x)-(27/16)=0 | | 4U^2-19u+15=0 | | 5x-37=7x+47 | | 3x/5=11 | | 1-4x=22-3x | | 1-4x=22-3z | | x-5=15-3x | | (x-1)/7*(2x-2)/49 | | 3-9x=1-x | | 4(x+5)=2(x-7) | | 17x-2=12x-1 | | y-10=30 | | 4e-3(2e-2)=3(e+8) | | 3(4d-2)=3(d-2) | | 5(c-2)=3(c+6) | | 15x-4+4x+5+65= | | 7(b-4)=5(b-2) | | 2(3b-4)=5(b-1) | | 3(3a+1)=30 | | 4(1/3x-1/4)+4/3x/3+1=6 | | 8-4=6z-8z | | k^3+2k^2-10k-20=0 | | 7(x+2)=7x+10 | | z^4-26z^2+25=0 | | 5x-10-2=13 | | 1/2x16=0 | | p^(2/3)+p^(1/2) | | 3x-7+5=16 | | (x^2-81)/(x^2-6x-27)*(x+3)/x | | 98x+456= |

Equations solver categories